Hydrodynamic Performance of an Undulatory Robot: Functional Roles of the Body and Caudal Fin Locomotion. (3rd January 2013) - Wen, Li; Liang, Jianhong; Shen, Qi; Bao, Lei; Zhang, Qian
Both body undulation and caudal fin flapping play essential locomotive roles while a fish is swimming, but how these two affect the swimming performance and hydrodynamics of fish individually is yet to be known. We implemented a biomimetic robotic fish that travel along a servo towing system, which can be regarded as "treadmill" of the model. Hydrodynamics was studied as a function of the principal kinetic parameters of the undulatory body and caudal fin of the model in a self-propelled condition, under which the time-averaged measured axial net force becomes zero. Thrust efficiency was estimated from two-dimensional digital particle image velocimetry (DPIV) measurements in the horizontal and mid-caudal fin plane. The Single-Row Reverse Karman wake (2S) is commonly observed in many previous studies of live fish swimming. However, we show that a Double-Row Two-Paired vortices (2P) wake was generated by the robotic model for most kinetic parameter combinations. Interestingly, the 2S wake emerged within the results of a narrow range of robotic caudal fin pitch angles (0<0<10°), occurring concurrently with enhanced thrust efficiency. We also show that, compared with the effect of body wavelength ( ? ), the wake structure behind the robotic swimmer is more sensitive to the Strouhal number ( St ) and caudal fin pitch angle ( θ ).